Deformation behaviour of AZ31 magnesium alloy sheet hybrid actuating with Al driver sheet and temperature in magnetic pulse forming. (January 2019) - Xu, Junrui; Xie, Xueyun; Wen, Zhisheng; Cui, Junjia; Zhang, Xu; Zhu, Daibo; liu, Yang
Highlights: Equipment for magnetic pulse forming of AZ31 sheet hybrid actuating with Al driver sheet and temperature was established. 1 mm AA1060 sheet and 200 ℃ are optimum forming parameters. FLC increased by increasing the deformation temperature from 25 ℃ to 200 ℃. High strain rate effect, yield strength decreasing and grain refinement affect the formability of AZ31 sheet. Abstract: In this paper, formability of AZ31 sheet in magnetic pulse forming hybrid actuating with driver sheet and temperature were investigated. The effects of discharge parameters, driver sheet and temperature were investigated on bulging by the experimental analysis. Forming height, thickness of AA1060 driver sheet, forming limit curve (FLC), fracture morphology and microstructure were performed to analyze causes of deformation behaviour for driver sheet and temperature. Analysis of driver sheet and temperature effects reveals that the optimum thickness of the driver sheet and temperature are 1 mm and 200 ℃, respectively. The FLC results show increased by increasing temperature from 25 ℃ to 200 ℃, and then decreased by increasing the temperature such as 250 ℃. Compared with quasi-static forming, the temperature effect for formability is unremarkable in magnetic pulse forming with driver sheet. Demonstrating similar drawability and strechability of AZ31 sheet appeared. Microstructure reveals that high strain rate effect, yield strength decreasing (because of temperature effect) and grain refinement are main reasons to affect the formability of AZ31 sheet in magnetic pulse forming with driver sheet and temperature. However, dynamic recrystallization (DRX) is not observed which is usually accompanied at temperatures higher than 150 ℃ in quasi-static forming.